PROSPEK PENGEMBANGAN USAHA PEMBENIHAN IKAN MAS (Cyprinus carpio L) DALAM KOLAM DI DESA PONORAGAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Rijal Wahyu Subekti; Muhammad Syafril; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
This research aims to find out the financial prospect of goldfish (Cyprinus carpio L) hatchery business development in the future. Results of research showed that goldfish (Cyprinus carpio L) hatchery business development in the pond is able to give financial benefits for the farmers in the future so that this development is financially feasible to continue. The hatchery business development is in the economic scale. The marketing areas of goldfish breeding include Loa Kulu, Sanga-sanga, Samarinda City, Balikpapan, Bontang and Sangatta.